(3eNJUQ UhGf GdMceI ddSLRis - (3Rjf GdOjf YeQ Hf SgdGf GdSGhi (B[(3GdSGLGhi (B]s; (3GdSLRj , WGgQ Hf EHQGgje Hf eMeO Hf WGgQ GdSLRj, CHh GdMSjfs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf , hUdhGJg Ydi NjQ Ndbg eMeO GdfHi GdCejf hBdg GdWjHjf GdWGgQjf s
(3BNQgG (B:s
(3Je GdcJGH HMeO Gddg hefg hMSf JhajbI , hUdi Gddg Ydi SjOfG eMeO GdfHi GdCei GdJgGei GdCHWMi GdReRei GdbQTi hBdg eUGHjM GdOLi GdWjHjf GdWGgQjf s
(3jdi Pdc (B: (3bUjOI GdEeGe CHj GdaJM GdHSJi Ke bUjOI CHj gGTe ESeGYjd Hf eMeO Hf jRjO Hf hOGY eaQY GdMejQi Ke fHPI efbhdI ef cJGH GdPNGFQ dGHf OQjOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B32s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B595 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B136 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdaGJM (B(3222) s
Keywords: (3GdJGQjNs